2017
DOI: 10.18632/oncotarget.15804
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of p38 MAPK contributes to stem cell-like properties of non-small cell lung cancer

Abstract: Cancer stem cells (CSCs) are recognized as the major source for cancer initiation and recurrence. Yet, the mechanism by which the cancer stem cell properties are acquired and maintained in a cancer cell population is not well understood. In the current study, we observed that the level of active p38 MAPK is downregulated, while the level of the stemness marker SOX2 is upregulated in lung cancer tissues as compared to normal tissues. We further demonstrated that inactivation of p38 is a potential mechanism cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…[30][31][32] Consistent with the tumor-inhibiting effect of p38 on human cancer, we previously reported that the level of activated/ phosphorylated p38 (p-p38) was reduced in NSCLC tissue samples compared with normal/normal adjacent lung tissue samples (N/ NAT). 25 To explore the mechanism responsible for the downregulation of p38 activity in NSCLC, we investigated the relationship between WIP1, a p38 phosphatase overexpressed in cancer, and p-p38. We first performed immunohistochemistry to examine the expression of WIP1 in human lung cancer samples with a tissue array containing 116 NSCLC tumor tissue samples (60 squamous cell carcinoma and 56 adenocarcinoma specimens) and 16 normal lung tissues/normal adjacent lung tissue samples (N/NAT) (4N and 12 NAT specimens) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[30][31][32] Consistent with the tumor-inhibiting effect of p38 on human cancer, we previously reported that the level of activated/ phosphorylated p38 (p-p38) was reduced in NSCLC tissue samples compared with normal/normal adjacent lung tissue samples (N/ NAT). 25 To explore the mechanism responsible for the downregulation of p38 activity in NSCLC, we investigated the relationship between WIP1, a p38 phosphatase overexpressed in cancer, and p-p38. We first performed immunohistochemistry to examine the expression of WIP1 in human lung cancer samples with a tissue array containing 116 NSCLC tumor tissue samples (60 squamous cell carcinoma and 56 adenocarcinoma specimens) and 16 normal lung tissues/normal adjacent lung tissue samples (N/NAT) (4N and 12 NAT specimens) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1b), as we reported previously. 25 Next, we divided the 116 NSCLC tumor tissue samples into two groups (high and low) based on their immunohistochemical staining scores for WIP1. The percentages of cases with high or low p-p38 levels were calculated by their staining scores in each group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations